The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pone.0257096
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, beliefs, attitudes and perceived risk about COVID-19 vaccine and determinants of COVID-19 vaccine acceptance in Bangladesh

Abstract: Bangladesh govt. launched a nationwide vaccination drive against SARS-CoV-2 infection from early February 2021. The objectives of this study were to evaluate the acceptance of the COVID-19 vaccines and examine the factors associated with the acceptance in Bangladesh. In between January 30 to February 6, 2021, we conducted a web-based anonymous cross-sectional survey among the Bangladeshi general population. At the start of the survey, there was a detailed consent section that explained the study’s intent, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
4
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 31 publications
8
96
4
6
Order By: Relevance
“…An online-based survey study involving 605 respondents that was conducted during January-February 2021 showed an overall rate for COVID-19 vaccine acceptance of 61.2%. 52 Another study from the country using face-to-face interviews and involved 1134 participants from the general population in January 2021 showed an overall COVID-19 vaccine acceptance rate of 67.5%. 53 In a larger study that used both online and face-to-face interviews and was conducted during January-February 2021 involving 4175 respondents, the COVID-19 vaccine acceptance rate was 60.5%.…”
Section: Bangladeshmentioning
confidence: 99%
“…An online-based survey study involving 605 respondents that was conducted during January-February 2021 showed an overall rate for COVID-19 vaccine acceptance of 61.2%. 52 Another study from the country using face-to-face interviews and involved 1134 participants from the general population in January 2021 showed an overall COVID-19 vaccine acceptance rate of 67.5%. 53 In a larger study that used both online and face-to-face interviews and was conducted during January-February 2021 involving 4175 respondents, the COVID-19 vaccine acceptance rate was 60.5%.…”
Section: Bangladeshmentioning
confidence: 99%
“…We argue for caution when using threat messages to promote vaccination willingness, because exaggerated or incorrect messaging could fuel vaccine skepticism and erode public trust, which are in turn two other important factors predicting vaccination willingness (Daly et al, 2021;Lindholt et al, 2020). Alternatively, it is possible that people who have low fear of COVID-19 have incorrect ideas about the potential dangers of COVID-19 for their own health and the health of their loved ones (Bono et al, 2021;Gallè et al, 2021;Mahmud et al, 2021). Information campaigns addressing such misconceptions may be a more appropriate way to bring threat perceptions in line with the objective risks and thereby increasing vaccination willingness and compliance with public health measures (Gallè et al, 2021;Huynh et al, 2021;Mahmud et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that people who have low fear of COVID-19 have incorrect ideas about the potential dangers of COVID-19 for their own health and the health of their loved ones (Bono et al, 2021;Gallè et al, 2021;Mahmud et al, 2021). Information campaigns addressing such misconceptions may be a more appropriate way to bring threat perceptions in line with the objective risks and thereby increasing vaccination willingness and compliance with public health measures (Gallè et al, 2021;Huynh et al, 2021;Mahmud et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The statistical significance of the correlation between socio-demographic factors and knowledge of the respondents and their practice and attitude towards TB was inspected using the Chi-square test. All the significant factors at a 10% level of significance in the Chi-square test were included in the univariate logistic regressions [23]. We did so to recheck the association between socio-demographic factors and knowledge of the respondents and their practice and attitude towards TB.…”
Section: Methodsmentioning
confidence: 99%